Determinants of pregnant women’s online self-regulatory activities for appropriate gestational weight gain - Kim, Hye Kyung (2015)
This study examined psychosocial and socio-demographic factors associated with pregnant women’s use of web-based tools to set and monitor personal goals for healthy diet and physical activity. These tools were made available to women participating in a randomized trial testing a web-based intervention to promote appropriate gestational weight gain. We used data from a baseline survey of pregnant women assigned to the intervention group and log data on women’s use of various intervention features (N = 873). Women who believed that appropriate gestational weight gain would lead to healthy outcomes for their child were more likely to engage in online goal-setting and self-monitoring. Less positive outcome expectancy beliefs about the relationship between their own weight and baby’s health partially explains why some at risk subpopulations (e.g., African-American women) were less likely to utilize online self-regulatory tools. This study specifies key psychosocial and motivational factors that guide the construction and monitoring of goals among pregnant women. These findings offer guidance for the design of interventions to promote self-regulatory techniques by identifying groups for whom those features are most likely to be useful, as well as psychological determinants of their use.